2011
DOI: 10.1149/1.3518756
|View full text |Cite
|
Sign up to set email alerts
|

Study on Redox, Structural and Electrical Properties of Ce[sub x]Zr[sub 1−x]O[sub 2] for Applications in SOFC Anodes

Abstract: The effect of redox cycles on the reducibility, structural, and electrical properties of dense pellets of ceria-zirconia solid solutions has been investigated by temperature programmed reduction studies, X-ray diffraction technique, Raman spectroscopy, and electrochemical impedance spectroscopy. Similarities and differences among the compositions with high ͑Ce 0.80 Zr 0.20 O 2 ͒, intermediate ͑Ce 0.50 Zr 0.50 O 2 ͒, and low ͑Ce 0.20 Zr 0.80 O 2 ͒ amounts of ceria were evaluated in view of their application as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Only a few studies investigated the correlations between water splitting performance and structural/compositional modification undergone during the redox steps, 23,25 despite that it is well-known that the redox properties of the materials are markedly affected by the thermal and redox history. 26 In a recent communication, we showed that also zirconia-rich ceria−zirconia mixed oxides can be suitable for the WS process. 27 In that study, it appeared clear that phase segregation and nitridation processes, which were induced by the thermal redox cycles, might play a major role in determining the high activity.…”
Section: ■ Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Only a few studies investigated the correlations between water splitting performance and structural/compositional modification undergone during the redox steps, 23,25 despite that it is well-known that the redox properties of the materials are markedly affected by the thermal and redox history. 26 In a recent communication, we showed that also zirconia-rich ceria−zirconia mixed oxides can be suitable for the WS process. 27 In that study, it appeared clear that phase segregation and nitridation processes, which were induced by the thermal redox cycles, might play a major role in determining the high activity.…”
Section: ■ Introductionmentioning
confidence: 97%
“…Most of the research has been focused on ceria-rich compositions, which were supposed to be structurally stable to the high temperatures adopted in the reduction step, and the attention of scientists was mainly drawn on kinetic and thermodynamic issues of the cycle. Only a few studies investigated the correlations between water splitting performance and structural/compositional modification undergone during the redox steps, , despite that it is well-known that the redox properties of the materials are markedly affected by the thermal and redox history . In a recent communication, we showed that also zirconia-rich ceria–zirconia mixed oxides can be suitable for the WS process .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ce 0.75 Zr 0.25 O 2Àd was used as the ceramic component of the Ni-cermet anodes to enhance the gasesolid interaction via H 2 adsorption on the ceramic components, promote hydrogen electro-oxidation via an oxygen spillover mechanism and thereby reduce the anode polarization resistances [19]. Boaro et al demonstrated that redox cycling at 973 K conduced to activation and stabilization of Ce 0.5 Zr 0.5 O 2Àd -Cu anodes, resulting from a rearrangement of the morphology and microstructure of Ce 0.5 Zr 0.5 O 2Àd oxides at the electrode/electrolyte interface and diffusion of more copper into the porous electrode matrix [18]. Recently, we have proposed a dual-scale hierarchical anode with nanoporous catalysts coated inside the macroporous 430L stainless steel scaffolds [23e25].…”
Section: Introductionmentioning
confidence: 99%
“…The relative kinetic relevance of these two processes depends not only on the identity and concentration of the reductant/oxidant and the CZO surface-to-volume ratio but also on the extent of reduction (ξ red ). CZO (and CeO 2 ) exhibit highly nonideal thermodynamics [10][11][12][20][21][22][23]28,41,42 with Gibbs free energies for O-removal that increase strongly as O-atoms are removed, and this nonideal behavior plausibly also affects the mobility and the reactivity of remaining O-atoms/O-vacancies such that they also depend strongly on ξ red , as predicted by (linear) free energy relationships. 43 These effects become discernible and "separable" only by considering chemical and transport dynamics driven by gradients in chemical potential that are pertinent for thermodynamically nonideal systems, for which the mobility and reactivity of O-atoms depend sensitively on the extent of reduction.…”
Section: O-atom Removal and Additionmentioning
confidence: 99%